1958
DOI: 10.1113/jphysiol.1958.sp006113
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and reflex secretion by the parotid gland in ruminants

Abstract: The parotid glands of adult ruminants secrete saliva rapidly and continuously. The Coats et al. (1956) found that although chemical, electrical or mechanical stimulation of the mouths of sheep sometimes increased the rate of parotid secretion, such stimuli were ineffective when applied to the rumen.The experiments described in this paper confirm and extend earlier work on the secretion of parotid saliva in sheep and define some of the reflex mechanisms which influence the rate of secretion. Observations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

1960
1960
1989
1989

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 14 publications
3
46
0
Order By: Relevance
“…Such would be the case if receptors were located elsewhere than the buccal cavity and in this respect it may be pertinent to note that sensory nerve endings have, in fact, been demonstrated in the reticulorumen epithelium (Hill, 1959b). Whether these are concerned in the reflex control of gastric secretion remains to be seen but it is of interest that vagal afferents concerned with salivary secretion have already been described in the reticulo-rumen (Kay, 1958). Harper, Kidd & Scratcherd (1959) have also shown that stimulation of the central end of the abdominal vagus in the cat causes secretion of acid and pepsin in the gastric juice.…”
Section: Discijssionmentioning
confidence: 99%
“…Such would be the case if receptors were located elsewhere than the buccal cavity and in this respect it may be pertinent to note that sensory nerve endings have, in fact, been demonstrated in the reticulorumen epithelium (Hill, 1959b). Whether these are concerned in the reflex control of gastric secretion remains to be seen but it is of interest that vagal afferents concerned with salivary secretion have already been described in the reticulo-rumen (Kay, 1958). Harper, Kidd & Scratcherd (1959) have also shown that stimulation of the central end of the abdominal vagus in the cat causes secretion of acid and pepsin in the gastric juice.…”
Section: Discijssionmentioning
confidence: 99%
“…The ability to secrete is especially poorly developed during the first 5 weeks of life, when there is almost no continuous secretion and the response to stimulation is only about one third of that of an equal weight of adult parotid tissue. In young calves also the parotid glands secrete slowly if at all (Epaneshnikov, 1935;Kay, 1958b) and it is possible that they develop less rapidly than in the goat for Kay & Phillipson (1959) found that the maximum rate of secretion by reflexly stimulated parotid glands (ml./g. hr) is considerably less in calves from 4 to 8 months old than in adult sheep.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of ruminal digestion introduces nervous and possibly humoral factors which may augment self-differentiation (Borghese, 1950) and inductive processes in determining the rate of growth and differentiation of the parotid gland. The chewing of solid food, rumination and the presence of digesta in the forestomach will cause reflex stimulation of the parotid gland from the sensory areas of the mouth, oesophagus and forestomach (Clark & Weiss, 1952;Kay 1958b; Ash & Kay, 1959) that will have been almost wholly lacking when only milk was consumed. The existence of a humoral factor influencing parotid secretion was claimed by Krinitsin (1940), who showed that the rate of secretion of the denervated parotid gland declines little in calves that are fed normally but almost ceased in calves that fasted for 5 days following bilateral vagotomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations